2016
DOI: 10.15407/ubj88.03.066
|View full text |Cite
|
Sign up to set email alerts
|

Expression of IGFBP6, IGFBP7, NOV, CYR61, WISP1 and WISP2 genes in U87 glioma cells in glutamine deprivation condition

Abstract: We have studied gene expression of insulin-like growth factor binding proteins in U87 glioma cells upon glutamine deprivation depending on the inhibition of IRE1 (inositol requiring enzyme-1), a central mediator of endoplasmic reticulum stress. We have shown that exposure of control glioma cells upon glutamine deprivation leads to down-regulation of NOV/IGFBP9, WISP1 and WISP2 gene expressions and up-regulation of CYR61/IGFBP10 gene expression at the mRNA level. At the same time, the expression of IGFBP6 and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
2
0
1
Order By: Relevance
“…It was also shown that knockdown of GLO1 in the cancer cells increases methylglyoxal level and significantly reduced tumor-associated properties such as migration and proliferation [26]. Therefore, our results concerning strong down-regulation of GLO1 gene expressions in glioma cells upon inhibition of ERN1 as well as upon glutamine withdrawal completely agree with functional role of this protein in tumor cells and with suppression of ERN1 knockdown glioma cell proliferation [7,12,22,25,26]. Therefore, the changes in expression level of genes encoding ATF6, EIF2AK3/PERK, GLO1, BIRC5/survivin, RAB5C, HSPB8, and HSPA5/BiP/ GRP78 proteins possibly reflect metabolic reprogramming of glioma cells by glutamine deprivation as well as ERN1-mediated endoplasmic reticulum stress signaling and correlate with suppression of glioma cell proliferation upon inhibition of the ERN1 signaling enzyme.…”
Section: Fig 3 Effect Of Glutamine Deprivation On the Expression Lesupporting
confidence: 82%
See 1 more Smart Citation
“…It was also shown that knockdown of GLO1 in the cancer cells increases methylglyoxal level and significantly reduced tumor-associated properties such as migration and proliferation [26]. Therefore, our results concerning strong down-regulation of GLO1 gene expressions in glioma cells upon inhibition of ERN1 as well as upon glutamine withdrawal completely agree with functional role of this protein in tumor cells and with suppression of ERN1 knockdown glioma cell proliferation [7,12,22,25,26]. Therefore, the changes in expression level of genes encoding ATF6, EIF2AK3/PERK, GLO1, BIRC5/survivin, RAB5C, HSPB8, and HSPA5/BiP/ GRP78 proteins possibly reflect metabolic reprogramming of glioma cells by glutamine deprivation as well as ERN1-mediated endoplasmic reticulum stress signaling and correlate with suppression of glioma cell proliferation upon inhibition of the ERN1 signaling enzyme.…”
Section: Fig 3 Effect Of Glutamine Deprivation On the Expression Lesupporting
confidence: 82%
“…Previously was shown that glutamine withdrawal affected the expression of several tumor growth related genes and that the effect of glutamine deprivation on most of these genes expression is dependent on ERN1 signaling enzyme function [19][20][21][22][23]. However, the regulation of the expression of many other tumor growth related genes by glutamine deprivation in relation to inhibition of ERN1 to not to be clarified yet.…”
Section: The Expression Of a Subset Of Genes Encoding Important Tumormentioning
confidence: 99%
“…Up to now, the role of WISP2 in ESCC is unelucidated, although the function of WISP2/CCN5 was explored in a variety of human cancers [8][9][10] .…”
Section: Discussionmentioning
confidence: 99%
“…У той самий час, рівень експресії генів антипроліферативних факторів (IGFВР3, IGFВР4 і IGFВР5) підвищується за умов пригнічення ензиму ЕRN1. Результати досліджень, одержані у відділі, дали можливість виявити роль ключових регулятор-них протеїнів системи IGF в ланцюжку подій, що пов'язують пригнічення функціональної активності сенсорно-сигнального ензиму стре-су ендоплазматичного ретикулума ERN1 та протипухлинні ефекти на рівні клітини, а та-кож молекулярні механізми впливу гіпоксії, дефіциту глюкози і глутамату на основну сиг-нальну систему відповіді клітин на ендоплазма-тичний стрес -ERN1 [16,17].…”
Section: -фосфофрукто-2-кінази/фруктозо-26-бісфосфатази-4 (рFkfв-4)unclassified